A Retrospective Analysis of Blood Lead Levels in Newly Arrived Immigrant Children, Miami-Dade County, Florida, 2013-2016 - Gwynn, Lisa (Public Health Rep, 2020)
OBJECTIVE: The Centers for Disease Control and Prevention’s (CDC’s) recommendation for blood lead level (BLL) screening of refugee children is to test new arrivals aged 6 months to 16 years. No such recommendations exist for testing immigrant children. Our objective was to provide evidence in support of creating lower age-specific guidelines for BLL screening for newly arrived immigrant populations to reduce the burden of unnecessary BLL testing. METHODS: We conducted a 3-year (2013-2016) retrospective analysis of BLLs of 1349 newly arrived immigrant children, adolescents, and young adults aged 3-19 who visited the University of Miami Pediatric Mobile Clinic in Miami, Florida. We obtained capillary samples and confirmed values >5 μg/dL via venous sample. The primary outcome was BLL in μg/dL. The main predictor variable was age. We further adjusted regression models by poverty level, sex, and ethnicity. RESULTS: Of 15 patients with a BLL that warranted further workup and a lead level of concern, 9 were aged 3-5 and 6 were aged 6-11. None of the adolescent and young adult patients aged 12-19 had a lead level of concern. Nearly half of the patients (n = 658, 48.8%) lived in zip codes of middle to high levels of poverty. CONCLUSION: This study provides evidence to support the creation of lower age-specific guidelines for BLL screening among newly arrived immigrant children and adolescents. Future studies should elucidate appropriate age ranges for BLL testing based on epidemiologic evidence, such as age and country of origin.